Search Equilibrium, Production Parameters and Social Returns to Education: Theory and Estimation - Christian Holzner; Andrey Launov (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
We introduce skill groups and different production technologies into the Burdett-Mortensen model of on the job search. Supermodularity of the different skill groups in the production process leads to a positive intra-firm wage correlation between skill groups. Increasing returns to scale allow the theoretical earnings density to be unimodal with a long right tail even in the absence of productivity dispersion. We perform the structural estimation the model and evaluate the effect that arises from the marginal shift of the skill structure towards larger fraction of high-skilled workers. Our estimates of the production parameters demonstrate economy-wide increasing returns to scale.
Keywords: J21; J23; J64; 330; Search; wage correlation; social returns to education